Digitalisasi dan Legalitas Praktik Dokter Gigi untuk Penguatan Daya Saing Layanan Kesehatan Pada Family Dental Care - Dina Maria Ulfa; Intan Umull Magfira Sary; Agung Winarno; Agus Hermawan (Pusat Riset dan Inovasi Nasional, 2025)
Small and medium enterprises (SMEs) in the healthcare sector, including independent dental practices, have experienced significant growth following the COVID-19 pandemic due to increased public awareness of disease prevention. However, this sector still faces challenges in complying with legal regulations and adapting to digital innovation to maintain competitiveness. Provisions such as the Medical Practice Law and various regulations from the Minister of Health require compliance with facility standards, medical waste management, and patient protection as requirements for obtaining operational permits. Furthermore, utilising digital technology through online promotions, social media, and electronic communications is a crucial strategy for attracting younger generations and building a professional image. Studies show that this approach can strengthen public engagement and trust in healthcare services. The case of the relocation of a family dental clinic in Malang City illustrates these challenges, particularly in terms of legal compliance and the use of digital media. Through a legal and digitalisation assistance programme, the clinic was supported in preparing legal documents such as hazardous waste agreements, pharmacy partnerships, and standard operating procedures. Furthermore, a digital marketing strategy was designed to strengthen brand identity and increase engagement on social media. As a result, the clinic demonstrated significant progress in legal readiness and improved digital image, although minor improvements are still needed. This programme demonstrates that the synergy between regulatory compliance and digital transformation can be a crucial foundation for the sustainability and competitiveness of healthcare SMEs in the modern era.